Negotiating Digital Pedagogy, Academic Adab, And Digital Integrity In Islamic Education Master’s Programs - Dina Maryana; Eva Desriyani; Ediah Marita; Dian Chilia Evanius Vista Arzela; Hendra Gunawan; Dwi Noviatul Zahra; Tri Hariyati; Khairunesa Isa (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze how digital pedagogy is negotiated in the Master’s Program of Islamic Religious Education through the use of digital platforms, academic adab, and digital integrity. The study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observation, and documentation involving lecturers, postgraduate students, academic managers, and relevant academic documents. The data were analyzed through data condensation, data display, and conclusion drawing, while credibility was strengthened through source and technique triangulation. The findings show that digital platforms support flexibility, accessibility, academic communication, assignment management, and collaborative learning in postgraduate Islamic education. However, platform use also requires strong pedagogical guidance to prevent passive participation, fragmented interaction, and merely administrative learning practices. The study further reveals that academic adab remains essential in maintaining respectful communication, disciplined participation, ethical dialogue, proper citation, and responsibility in digital academic spaces. In addition, digital integrity becomes increasingly urgent due to the growing use of online resources and artificial intelligence tools, which require students to maintain originality, verify sources, and distinguish academic assistance from authorship. This study implies that Islamic higher education institutions need clear guidelines for digital learning, academic ethics, and responsible AI-assisted academic work.